TINJAUAN PENGGUNAAN SARANA TENIS MEJA DALAM PEMBELAJARAN PENJAS PADA SISWA KELAS X SMA NEGERI 1 KUPANG - Oktavianus Lede; Agustinus J Nafie; Benediktus Ndolu (Nusa Cendana University, 2020)
Based on the problem definition, the problem is formulated as follows: How to use the Physical Education table tennis facility in SMA Negeri I Kupang. In its implementation, physical education uses direct practice with gestures or physical activities as the main media to achieve learning objectives at SMA Negeri 1 Kupang. Activities carried out in physical education learning can be done using a learning approach in each sport. One of the sports that is usually taught in physical education learning in formal schools is table tennis. Table tennis is a simple game. Table tennis was originally known as a means of light entertainment for the community, there are no formal / official rules regarding the size of the court, hitter, net, ball, and other equipment. The method used is a qualitative method by means of observation, in-depth interviews and support. From the direct research results, it is concluded that during the learning process, a professional teacher who can implement the basic techniques of table tennis in Physical Education learning at SMA Negeri 1 Kupang is needed. Therefore, the government needs a role in dealing with this in order to create an effective learning process at SMA Negeri 1 Kupang.